GIS mapping of the moraines of the Mont-Blanc and Aiguilles Rouges massifs - Quentin Portal; Jean-François Buoncristiani (PANGAEA, 2024)
This dataset is a shapefile (polyline) of the moraine ridges of the Mont-Blanc and Aiguilles-Rouges massifs (French, Italian and Swiss Alps) intended to be as exhaustive as possible. This dataset was produced during a master extquotesingles internship in order to have a global overview of all the moraines in the area on GIS support. The main objective was to compare the moraine deposits of two periods: the Younger Dryas and the end of the Holocene (Neoglacial). The mapping was carried out at the scale of the two massifs using high-resolution DEMs (LiDAR HD, France; DTM 2005/2008, Italy; swissALTI3D, Switzerland) and geological maps. The deposition period was inferred when possible using absolute dating and geomorphological reconstructions (Gardent, 2014; Le Roy et al., 2015, doi:10.1016/j.quascirev.2014.10.033; Protin et al., 2019, doi:10.1016/j.quascirev.2019.105863, 2021, doi:10.1111/bor.12519; Serra et al., 2022, doi:10.1016/j.quascirev.2022.107446). The attribute table contains the following elements: moraine deposition period (Younger Dryas, Neoglaciation or unknown), name of the associated glacier, massif (Mont-Blanc or Aiguilles Rouges).